McKinsey & company : hard lessons learned in South Africa - Sieff, Grant; Bowen, Amanda (London : Wits Business School, 2019)
On 18 June 2019, the Gauteng High Court "set aside and declared unlawful all the decision-making processes through which Eskom had concluded [a] contract with McKinsey".
Description based on XML content.
Keywords: elektronické knihy; electronic books; Decision making